2005
DOI: 10.1126/science.1101160
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CCL3L1 Gene-Containing Segmental Duplications on HIV-1/AIDS Susceptibility

Abstract: Segmental duplications in the human genome are selectively enriched for genes involved in immunity, although the phenotypic consequences for host defense are unknown. We show that there are significant interindividual and interpopulation differences in the copy number of a segmental duplication encompassing the gene encoding CCL3L1 (MIP-1alphaP), a potent human immunodeficiency virus-1 (HIV-1)-suppressive chemokine and ligand for the HIV coreceptor CCR5. Possession of a CCL3L1 copy number lower than the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
918
2
7

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,019 publications
(962 citation statements)
references
References 21 publications
35
918
2
7
Order By: Relevance
“…The similarity of the population CNV distribution between CCL4L and CCL3L performed in the same set of individuals is noteworthy. 21 To give a more general view of the worldwide distribution of CCL4L copy number, individuals were pooled into seven broad continental regions and the mean of CCL4L copy number was calculated. Sub-Saharan African populations display the highest number of CCL4L copies (mean ¼ 4.32 ± 0.63, including individuals with 8, 9 or 10 copies), whereas Europe present the lowest copy number (1.89 ± 0.40), including a 25% of individuals with only one CCL4L copy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The similarity of the population CNV distribution between CCL4L and CCL3L performed in the same set of individuals is noteworthy. 21 To give a more general view of the worldwide distribution of CCL4L copy number, individuals were pooled into seven broad continental regions and the mean of CCL4L copy number was calculated. Sub-Saharan African populations display the highest number of CCL4L copies (mean ¼ 4.32 ± 0.63, including individuals with 8, 9 or 10 copies), whereas Europe present the lowest copy number (1.89 ± 0.40), including a 25% of individuals with only one CCL4L copy.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Recently, the widespread presence of CNVs in the genomes of healthy individuals with no obvious genetic disorders has been described in a few populations, 1,2 but relatively few data has been reported regarding CNVs and disease resistance or susceptibility. 9,21 Regarding this point, the main aim of our work was to link the analysis of SNPs and CNVs within a worldwide framework to achieve a more powerful tool in the future determination of genetic basis of susceptibility or resistance to disease. It seems clear that genes with CNV require a nonconventional method to study their SNPs, and this is the reason why we established a clear and precise approach to solve this problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[162][163][164][165][166] In addition, one study has shown the correlations of about 30 SNPs (that found to be associated with various traits by GWAS) with CNVs at r 2 40.5, this provides preliminary evidence of the associations and possible roles of CNVs in human complex traits. 161 The amount of evidence is expected to increase in the near future, when we have a better understanding of the characteristics of non-SNP variants and a more comprehensive map of them constructed upon the completion of the 1000 Genomes Project, and when more efficient and accurate methods are available to detect the non-SNP variants for disease-association studies.…”
Section: Non-snp Variants and Complex Diseasesmentioning
confidence: 81%